2013
DOI: 10.1088/0029-5515/53/8/083025
|View full text |Cite
|
Sign up to set email alerts
|

Fast-wave power flow along SOL field lines in NSTX and the associated power deposition profile across the SOL in front of the antenna

Abstract: Fast-wave heating and current drive efficiencies can be reduced by a number of processes in the vicinity of the antenna and in the scrape off layer (SOL). On NSTX from around 25% to more than 60% of the high-harmonic fast-wave power can be lost to the SOL regions, and a large part of this lost power flows along SOL magnetic field lines and is deposited in bright spirals on the divertor floor and ceiling. We show that field-line mapping matches the location of heat deposition on the lower divertor, albeit with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 28 publications
6
48
0
Order By: Relevance
“…The former is in agreement with the experimental observations found in NSTX [5,6,11,12,13] and DIII-D [9]. On the other hand, the latter is not easy to link directly to the experimental observations and additional studies might be required.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The former is in agreement with the experimental observations found in NSTX [5,6,11,12,13] and DIII-D [9]. On the other hand, the latter is not easy to link directly to the experimental observations and additional studies might be required.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the latter is not easy to link directly to the experimental observations and additional studies might be required. Recently, NSTX experiments have shown that HHFW power lost to the SOL flows from the NSTX antenna region to the hot spots in divertor region essentially along field lines [12,13]. In Alcator C-Mod strong ICRF-enhanced plasma potentials have been observed in the SOL regions that are not magnetically mapped to the active ICRF antennas [14].…”
Section: Discussionmentioning
confidence: 99%
“…This is about three times greater than the increment q P4 -q P2 computed above; however, this increment is observed to decrease as the second pass is moved to the region outside the gap by decreasing the magnetic field pitch in the SOL. 35 Lastly, we consider the IR measurements at Bay G top, where the first pass is located outboard of the vessel gap at a major radius close to the probe radii and exhibits a background of $0.2 MW/m 2 and an increment due to the RF of $0.1 MW/m 2 . These values are closer to those calculated from the IV characteristics.…”
Section: B Average Rf Heat Flux Transmissionmentioning
confidence: 99%
“…The SPIRAL code was used to map the magnetic field lines passing in the SOL in front of the antenna at the midplane to their strike points on the divertors, and indeed these strikepoints form a spiral (Fig. 12) [22,23]. The passes of this spiral line up with the IR camera peaks observed along a major radius view of the divertor floor [23].…”
Section: Nstx Tokamak: Transition To High Harmonic Fast Wave (Hhfw) Rmentioning
confidence: 99%
“…12) [22,23]. The passes of this spiral line up with the IR camera peaks observed along a major radius view of the divertor floor [23]. Furthermore, the RF effects for the lower spiral are observed on probe floating potentials and instrumented tile currents [22].…”
Section: Nstx Tokamak: Transition To High Harmonic Fast Wave (Hhfw) Rmentioning
confidence: 99%